+0  
 
0
407
2
avatar

1.). (x-5)^2=(2x-3)^2

2.). (x+3)(x-4)=(x-2)^2

3.). 5x(6x-10)=-3x(7x-2)

Plssss help

 Jun 22, 2017
 #1
avatar
0

1)    

Solve for x:
(x - 5)^2 = (2 x - 3)^2

Take the square root of both sides:
x - 5 = 2 x - 3 or x - 5 = 3 - 2 x

Subtract 2 x - 5 from both sides:
-x = 2 or x - 5 = 3 - 2 x

Multiply both sides by -1:
x = -2 or x - 5 = 3 - 2 x

Add 2 x + 5 to both sides:
x = -2 or 3 x = 8

Divide both sides by 3:
Answer: | x = -2 or x = 8/3

 

2) 

Solve for x:
(x - 4) (x + 3) = (x - 2)^2

Expand out terms of the left hand side:
x^2 - x - 12 = (x - 2)^2

Expand out terms of the right hand side:
x^2 - x - 12 = x^2 - 4 x + 4

Subtract x^2 - 4 x + 4 from both sides:
3 x - 16 = 0

Add 16 to both sides:
3 x = 16

Divide both sides by 3:
Answer: | x = 16/3

 

3)     

Solve for x:
5 x (6 x - 10) = -3 x (7 x - 2)

Expand out terms of the left hand side:
30 x^2 - 50 x = -3 x (7 x - 2)

Expand out terms of the right hand side:
30 x^2 - 50 x = 6 x - 21 x^2

Subtract 6 x - 21 x^2 from both sides:
51 x^2 - 56 x = 0

Factor x from the left hand side:
x (51 x - 56) = 0

Split into two equations:
x = 0 or 51 x - 56 = 0

Add 56 to both sides:
x = 0 or 51 x = 56

Divide both sides by 51:
Answer: | x = 0           or          x = 56/51

 Jun 22, 2017
 #2
avatar+98130 
+2

 

1.). (x-5)^2=(2x-3)^2  simplify

 

(x - 5)  ( x - 5)  = (2x - 3) (2x - 3)   expand

 

x^2 - 10x  +  25  =  4x^2 - 12x + 9      

 

0 = 3x^2  - 2x - 16    or

 

3x^2 - 2x  - 16  = 0

 

 

2.). (x+3)(x-4)=(x-2)^2  simplify

 

x^2 - x  - 12  =  (x -2) (x -2)

 

x^2 - x  -12   =  x^2   - 4x  + 4       

 

3x - 16  = 0

 

 

3.). 5x(6x-10) = -3x(7x-2)   simplify

 

30x^2 -  50x  =  -21x^2 +  6x     

 

51x^2 - 56x  = 0

 

 

 

cool cool cool

 Jun 22, 2017

4 Online Users

avatar